2011
DOI: 10.5127/jep.006610
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Method Evaluation of Distress Tolerance Measures and Construct(s): Concurrent Relations to Mood and Anxiety Psychopathology and Quality of Life

Abstract: Despite the growing theoretical and clinical interest in distress tolerance (DT) and its role(s) in psychopathology vulnerability, we lack knowledge regarding the: (1) nature and degree of associations between putatively related measures of DT, and (2) universal/differential nature of associations between these DT measures and psychopathological syndromes. Accordingly, the purpose of the current multimethod study was thus to investigate the relations between and among various self-report and behavioral DT meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 28 publications
10
70
0
Order By: Relevance
“…We see this distinction as comparable to Spielberger's conceptualization of state versus trait anxiety or state versus trait anger (Spielberger and Sydeman, 1994). Although Bernstein et al (2011) andMcHugh et al (2011) reported a similar association between self-report and behavioral measures of distress tolerance, they did not specifi cally conceptualize these as state versus trait differences. Although we equate state persistence with behavioral measures and trait measures with self-report measures, it is clear that self-report measures could be developed to measure state persistence.…”
Section: Discussionmentioning
confidence: 92%
“…We see this distinction as comparable to Spielberger's conceptualization of state versus trait anxiety or state versus trait anger (Spielberger and Sydeman, 1994). Although Bernstein et al (2011) andMcHugh et al (2011) reported a similar association between self-report and behavioral measures of distress tolerance, they did not specifi cally conceptualize these as state versus trait differences. Although we equate state persistence with behavioral measures and trait measures with self-report measures, it is clear that self-report measures could be developed to measure state persistence.…”
Section: Discussionmentioning
confidence: 92%
“…Further, work in a civilian community sample determined that perceived (i.e., self-report) DT for emotional stimuli, compared with actual, behaviorally observed DT or DT for physical stimuli, appears to be particularly relevant to PTSD symptom severity, after covarying for neuroticism, trauma load, and participant sex (Marshall-Berenz et al, 2010). It is important to note that self-report measures of DT and behavioral measures are generally uncorrelated (Bernstein, Marshall, & Zvolensky, 2011; Marshall-Berenz et al, 2010; McHugh et al, 2011), as they potentially assess different aspects of DT. Furthermore, they have been found to be differentially related to clinical outcomes, with self-report measures of DT often being related to PTSD and anxiety (Bernstein et al, 2011; Marshall-Berenz et al, 2010).…”
mentioning
confidence: 99%
“…In support of this, two investigations by Brandt and colleagues [37,38] suggest that both AS and ER evidence greater specificity to poor outcomes among HIV+ individuals, as compared with DT. Alternatively, the method of measurement of DT may have contributed to this null finding [28]. Given the observed differential relations between objective and subjective measures of DT among individuals with HIV [36], it is possible that including a multimethod assessment of DT in the present investigation would have provided more nuanced findings in terms of the importance of DT in the measured outcomes.…”
Section: Discussionmentioning
confidence: 59%
“…Exploring malleable (i.e., changeable via intervention) cognitive-affective vulnerability factors that have demonstrated both strong theoretical and empirical relations to a range of health risk behaviors (i.e., distress tolerance [10]; anxiety sensitivity, [11]; emotion regulation, [12]), may provide a novel and relevant avenue by which to develop more effective, specialized interventions for individuals with HIV. More specifically, interventions targeting behavioral, cognitive, and physical sequelae associated with HIV, including HIV symptom severity, perceived barriers to ART adherence, and disease presence, progression, and symptomatology, have the potential to result in numerous improvements in overall quality of life (e.g., [13]). …”
mentioning
confidence: 99%
See 1 more Smart Citation